Life Writing Therapy Decreases Depression in Late Adolescence - Zulaikah Nur Istiqomah; Erna Erawati; Suyanta Suyanta (Universitas Airlangga, 2018)
Introduction: Late adolescence (16-18 years old) usually experiences a crucial period in life which makes teenagers vulnerable to mood disorders such as depression. One of the interventions that can decrease depression is writing a memoir, biography, diary, and life writing. Writing can disclose the feeling and help mind care. The objective of this study was to investigate the influence of life writing therapy to decrease depression in late adolescence.Methods: This study used pretest-post-test control group design with 40 people as samples, divided into intervention and control groups. Before and after the treatment, both groups were measured using the scale of the PHQ-9A to see the depression in late adolescence of high school students.Results: Life writing therapy shows differences in mean between intervention group and control group with a p-value of 0.000 (α <0.05).Conclusion: The life writing therapy has an effect in reducing depression in students. It facilitates subjects to evaluate, analyze, and reassess past, current and future events so that subjects can get an understanding, develop a solution and self-motivation, accept the existing situation, learn from what is experienced, focus thoughts on positive things, and assess positive things from an event.